Abundância de larvas de Salminus brasiliensis em uma planície de inundação a jusante de barramento: variações espaço-temporais e influências abióticas - Balena, Ivonei Neunfeld (2013)
This study aims to evaluate the spatial and temporal distribution of larval Salminus brasiliensis in a region downstream of an impoundment. Through larval abundances were analyzed interannual and monthly variations, occurrences in the tributaries and canals of the Paraná River and possible influences of abiotic variables in cathes of larvae. Eighteen points were sampled monthly from October until March during the years 2001-2012, covering ten reproduction periods. The samplings were carried out nightly using a conical-cylindrical plankton nets mesh 0.5 mm equipped with mechanical flowmeter, and the abundances were standardized to 10m3 of water. With purpose to verify differences between the means of the spatial and temporal abundances of larvae and their relation to abiotic variables we used the nonparametric Krurskall- Wallis and Spearman correlation, respectively, since the variables did not meet the assumptions of normality (Shapiro-Wilk test) and homoscedasticity (Levene's test). It was possible to determine the period of greatest reproductive activity of S. brasiliensis, registering high abundances between October and January, last month featured be the peak of the spawns. There was also a reduction in annual catches suggesting a possible flaw in the reproductive process of the species caused apparently by level control influences, leading to a possible reduction of desovante stock in the region. There were no differences in larval drifts between the canals and tributaries were identified as spawning site and probably used as migratory routes for the species. Larval catches seem to have been mainly influenced by temperature and rainfall, a clue that these factors acted in triggering of spawns, but the lack of relationship with the fluviométrico level indicates that the increased rainfall is not reflecting in full, which apparently is compromising the reproduction of S. brasiliensis in the region, confirming the assumption that the dam has negatively influenced the reproduction of migratory species.